The Conciliation of Labour Disputes: I — Typical Cases - Ferland, Jean-Paul (Relations industrielles / Industrial Relations, 1951)
SummaryWe have asked, as a matter of interest to our readers, two Conciliators, graduated, one from Laval and the other from Montreal University and Queen's, who are officials of the Provincial Labour Department, to give their views on conciliation as it now stands, in the districts of Montreal and Quebec.